Variation in morpho-lexical development within and between diagnoses in children with neurodevelopmental disorders - Foster-Cohen, Susan; Macrae, Toby; Newbury, Jayne (Frontiers in Psychology, 2023)
While primary diagnosis is only one aspect of the presentation of a child with neurodevelopmental delay/disorder, the degree to which early expressive language reflects diagnostic divisions must be understood in order to reduce the risk of obscuring clinically important differences and similarities across diagnoses. We present original data from the New Zealand MacArthur-Bates Communicative Development Inventory from 88 English-speaking children aged 2;6 to 5;6 years receiving multidisciplinary intervention within a single family-centered program. The children had one of six pediatrician-assigned genetic or behaviorally determined diagnoses: Down syndrome; motor disorders (Cerebral Palsy and Developmental Coordination Disorder); Global Development Delay; disorders of Relating and Communicating; other genetically defined diagnoses; or language delay due to premature birth. Morphological and lexical development were compared within and across diagnostic groups, using both data visualization and mixed-effects modeling. Groups varied in the amount of variation within and between them, but only prematurity reached significance, in interaction with age, as a predictor of morpho-lexical scores. Further analysis of longitudinal data available from a subset of the sample (n = 62) suggested that individual trajectories of vocabulary growth could not be reliably predicted by diagnosis. Moreover, the distribution of word types (nouns, predicates, etc.) only distinguished premature children with language delay from those with DS and those in the Relating and Communicating group. There were strong similarities in early morpho-lexical development across these clinical populations, with some differences. These findings align with research and clinical approaches which accommodate individual variation within diagnosis, and broad similarities across diagnostic groups.